Viscosity Projection Algorithms for Pseudocontractive Mappings in Hilbert Spaces - Xiujuan Pan; Shin Min Kang; Young Chel Kwun (Abstract and Applied Analysis)
An explicit projection algorithm with viscosity technique is constructed for finding the fixed points of the pseudocontractive mapping in Hilbert spaces. Strong convergence theorem is demonstrated. Consequently, as an application, we can approximate to the minimum-norm fixed point of the pseudocontractive mapping.